Factor for Asset Valuation of Machinery and Equipment at Water Treatment Plant - Mahmud, Musliha; Omar, Abdul Jalil (Research in Management of Technology and Business, 2025)
Plant, Machinery and Equipment Assessment (LJP) is now a very important assessment branch especially for companies or a large industrial company that involves the operating process and water treatment plant are one of the elements of LJP that can be assessed for certain reasons. For this reason, this study will be conducted with the first objective of this study is to identify the factors that are taken into account in plant valuation. Further, for the second objective is to identify valuation methods for facility components in water treatment plants. The scope of this study involves all types of machinery components, equipment at the plant and involves several assessors in Malaysia. This study aims to identify the best valuation method to carry out plant valuation carried out by private appraisers as well as government appraisers. The findings for this study are based on a series of interviews conducted with four (4) respondents, from public assessment officers and private assessment officers.